2009
DOI: 10.1073/pnas.0810286106
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional structure of the human copper transporter hCTR1

Abstract: Copper uptake proteins (CTRs), mediate cellular acquisition of the essential metal copper in all eukaryotes. Here, we report the structure of the human CTR1 protein solved by electron crystallography to an in plane resolution of 7 Å. Reminiscent of the design of traditional ion channels, trimeric hCTR1 creates a pore that stretches across the membrane bilayer at the interface between the subunits. Assignment of the helices identifies the second transmembrane helix as the key element lining the pore, and reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
266
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 244 publications
(282 citation statements)
references
References 45 publications
13
266
0
3
Order By: Relevance
“…A study of hCTR1 mutants expressed in insect cells identified residues in or near the transmembrane domains that affect K m and or V max of 64 Cu uptake (14). These results and recent structural studies suggest that copper transits a pore lined by transmembrane segments two and three in the homotrimeric complex (8,9). Another mechanism based on endocytosis and degradation of hCTR1 has also been proposed (15).…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…A study of hCTR1 mutants expressed in insect cells identified residues in or near the transmembrane domains that affect K m and or V max of 64 Cu uptake (14). These results and recent structural studies suggest that copper transits a pore lined by transmembrane segments two and three in the homotrimeric complex (8,9). Another mechanism based on endocytosis and degradation of hCTR1 has also been proposed (15).…”
mentioning
confidence: 86%
“…Human copper transporter 1 (hCTR1) 2 and orthologous proteins throughout eukaryotes have three transmembrane segments (6,7) and form homotrimeric, membrane complexes (8,9) that carry out the high affinity transport of monovalent copper (see Fig. 1, inset).…”
mentioning
confidence: 99%
“…C. neoformans possesses two high-affinity Cu þ importers (Ctr1 and Ctr4) belonging to the Ctr family, which is conserved from yeast to mammals 12 . The Ctr family forms homotrimer structures to generate a Cu þ -importing channel 1,31 . Ctr1 and Ctr4 are independent and functionally redundant Cu þ importers whose expression is regulated by Cu 12,32 .…”
Section: Discussionmentioning
confidence: 99%
“…Low resolution cryoelectron microscopy studies of the 190-amino acid hCTR1 transporter show that the transporter is a homotrimer, in which the N terminus is extracellular, the transmembrane domains form the pore, and the short C-terminal tail is cytoplasmic (15,16). Previous biochemical studies suggested this topology (17)(18)(19), and multiple studies suggest that the second transmembrane domain lines the channel or pore (10,20,21).…”
mentioning
confidence: 99%